THE INVESTIGATION OF MICROORGANISMS IN FRESH VEGETABLES: BACTERIA AND FUNGI - Rezan Sabah Ahmed; Tablo Abdulrahim Ahmed (Acta Scientifica Malaysia)
The purpose of this study was to separate microorganisms (fungi and bacteria) from three distinct vegetables: celery, lettuce, and arugula. The Potato Dextrose Agar (PDA) method of the power plate method was utilized to isolate and identify various fungal species, and the same procedure was followed to isolate bacteria from the samples under study. The findings identify the fungi and display the total number of colony forming units (CFU) in three different vegetables grown on PDA medium. Rhizopus sp., Aspergillus sp., Alternaria, yeast, Penicillium, Alternaria, and Rhodotorula were the most often isolated fungi. Mucor and Demaceous were the less common species of fungi found. The first grocery store had celery with a higher count of bacteria—268 CFU. With 250 CFU, lettuce had the highest amount of bacteria in the second grocery. Additionally, celery was found to have a higher concentration of bacteria in the third grocery store—280 CFU.